Rearrange the following equation to make 'm' the subject: 4 (m - 2) = t (5m + 3) [4 marks]

Expand brackets on both sides:  4m − 8 = 5mt + 3t

Collect all terms containing 'm' to one side of the equation: 4m − 5mt = 8 + 3t

Factorise the terms containing 'm': m (4 − 5t) = 8 + 3t

Divide by factorised values: m = (8 + 3t) / (4 − 5t)

Answered by Nadia M. Maths tutor

3090 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

Factorise f(x) = 6x^3 -7x^2 -x +2 = 0


Solve 2x + 4 > 16


Solve for x in the following equation using the quadratic formula, completing the square and factoring method: 2x^2-x-1=0


Show that 12 cos 30° - 2 tan 60° can be written in the form root (k) where k is an integer.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences